Increased uptake of doxorubicin by cells undergoing heat stress does not explain its synergistic cytotoxicity with hyperthermia. (1st January 2019) - Sharma, Anirudh; Özayral, Sanem; Caserto, Julia S.; ten Cate, Rosemarie; Anders, Nicole M.; Barnett, James D.; Kandala, Sri Kamal; Henderson, Elizabeth; Stewart, Jacqueline; Liapi, Eleni; Rudek, Michelle A.; Franken, Nicolaas A.P.; et al.
Abstract: Purpose: A proposed mechanism for the enhanced effectiveness of hyperthermia and doxorubicin (Dox) combinations is increased intracellular Dox concentrations resulting from heat-induced cell stress. The purpose of this study was to determine whether specific varied Dox and heat combinations produce measurable effects greater than the additive combination, and whether these effects can be attributed to heat-induced increases in intracellular Dox concentrations. Methods: HCT116, HT29 and CT26 cells were exposed to Dox and water bath heating independently. A clonogenic survival assay was used to determine cell killing and intracellular Dox concentrations were measured in HCT116 cells with mass spectrometry. Cells were exposed to heating at 42 °C (60 min) and 0.5 µg/ml of Dox at varying intervals. Synergy was determined by curve-fitting and isobologram analysis. Results: All cell lines displayed synergistic effects of combined heating and Dox. A maximum synergistic effect was achieved with simultaneous cell exposure to Dox and heat. For exposures at 42 °C, the synergistic effect was most pronounced at Dox concentrations <0.5 µg/ml. Increased intracellular concentrations of Dox in HCT116 cells caused by heat-stress did not generate a concomitant thermal enhancement. Conclusions: Simultaneous exposure of HCT116 cells to heating and Dox is more effective than sequential exposure. Heat-induced cell responses are accompanied by increased intracellular Dox concentrations; however, clonogenic survival data do not support this as the cause for synergistic cytotoxicity.